Novel tools for genetic manipulation of follicle stem cells in the Drosophila ovary reveal an integrin-dependent transition from quiescence to proliferation. - Hartman, T.R.; Ventresca, E.M.; Hopkins, A.; Zinshteyn, D.; Singh, T.; O'Brien, J.A.; Neubert, B.C.; Hartman, M.G.; Schofield, H.K.; Stavrides, K.P.; Talbot, D.E.; Riggs, D.J.; et al. (Genetics, 2015)
In many tissues, the presence of stem cells is inferred by the capacity of the tissue to maintain homeostasis and undergo repair after injury. Isolation of self-renewing cells with the ability to generate the full array of cells within a given tissue strongly supports this idea, but the identification and genetic manipulation of individual stem cells within their niche remain a challenge. Here we present novel methods for marking and genetically altering epithelial follicle stem cells (FSCs) within the Drosophila ovary. Using these new tools, we define a sequential multistep process that comprises transitioning of FSCs from quiescence to proliferation. We further demonstrate that integrins are cell-autonomously required within FSCs to provide directional signals that are necessary at each step of this process. These methods may be used to define precise roles for specific genes in the sequential events that occur during FSC division after a period of quiescence.